Empirical Correlation between Geotechnical and Geophysical Parameters in a Landslide Zone (Case Study: Nargeschal Landslide) - Sadegh Rezaei; Issa Shooshpasha; Hamed Rezaei (Earth Sciences Research Journal)
Today, geotechnical and geophysical techniques are used for landslide evaluation. Geotechnical methods provide accurate data, but are time consuming and costly. Geophysical techniques, however, are fast and inexpensive, yet their accuracy is lower than that of the geotechnical methods. Therefore, simultaneous use of geotechnical and geophysical methods provides a suitable solution for landslide evaluation. Availability of geotechnical and geophysical data makes it possible to investigate correlation between different parameters. Correlating geotechnical and geophysical parameters ends up lowering field investigation costs and enhancing subsurface survey speed in a landslide zone. In the present study, in order to evaluate Nargeschal landslide in Iran, ambient noise measurement, ERT survey, and geotechnical investigations were used. Once finished with data processing, the data obtained from geotechnical and geophysical investigations were correlated. These included SPT-N – electrical resistivity, soil moisture content – electrical resistivity, and SPT-N – shear wave velocity correlations. The correlations were examined using two methods, namely Spearman’s coefficient test and least square regression analysis. The results obtained from the two methods were in good agreement with one another. The correlations obtained in this study were of moderate to very strong strength and fell in the range of the results of previous studies. Investigation of the results indicated significant influences of ground water on electrical resistivity and soil stiffness on shear wave velocity. Results of this study can be used for soil classification and determination of mechanical and seismic characteristics of soil across various areas.